Convergent Evidence That ZNF804A Is a Regulator of Pre-messenger RNA Processing and Gene Expression. (29th December 2018) - Chapman, Ria M; Tinsley, Caroline L; Hill, Matthew J; Forrest, Marc P; Tansey, Katherine E; Pardiñas, Antonio F; Rees, Elliott; Doyle, A Michelle; Wilkinson, Lawrence S; Owen, Michael J; O'Donovan, Michael C; Blake, Derek J
Abstract: Genome-wide association studies have linked common variation in ZNF804A with an increased risk of schizophrenia. However, little is known about the biology of ZNF804A and its role in schizophrenia. Here, we investigate the function of ZNF804A using a variety of complementary molecular techniques. We show that ZNF804A is a nuclear protein that interacts with neuronal RNA splicing factors and RNA-binding proteins including RBFOX1, which is also associated with schizophrenia, CELF3/4, components of the ubiquitin-proteasome system and the ZNF804A paralog, GPATCH8. GPATCH8 also interacts with splicing factors and is localized to nuclear speckles indicative of a role in pre-messenger RNA (mRNA) processing. Sequence analysis showed that GPATCH8 contains ultraconserved, alternatively spliced poison exons that are also regulated by RBFOX proteins. ZNF804A knockdown in SH-SY5Y cells resulted in robust changes in gene expression and pre-mRNA splicing converging on pathways associated with nervous system development, synaptic contact, and cell adhesion. We observed enrichment ( P = 1.66 × 10 –9 ) for differentially spliced genes in ZNF804A -depleted cells among genes that contain RBFOX-dependent alternatively spliced exons. Differentially spliced genes in ZNF804A -depleted cells were also enriched for genes harboring de novo loss of function mutations in autism spectrum disorder ( P = 6.25 × 10 –7, enrichment 2.16) and common variant alleles associated with schizophrenia ( P = .014), bipolar disorder and schizophrenia ( P = .003), and autism spectrum disorder ( P = .005). These data suggest that ZNF804A and its paralogs may interact with neuronal-splicing factors and RNA-binding proteins to regulate the expression of a subset of synaptic and neurodevelopmental genes.